A Detailed View on the Proanthocyanidins in Ginkgo Extract EGb 761 - Kulić, Žarko; Ritter, Thomas; Röck, Birgit; Elsäßer, Jens; Schneider, Heike; Germer, Stefan (Planta Medica, 2021)
The Ginkgo extract EGb 761® manufactured with leaves of Ginkgo biloba has been continuously produced over decades at a large scale and is used as a clinically proven remedy for, among other things, the improvement of age-associated cognitive impairment and quality of life in patients with mild dementia. It belongs to the class of extracts addressed as quantified extracts according to the European Pharmacopeia. Accordingly, several compounds (e.g., flavone glycosides and terpene trilactones) are acknowledged to contribute to its clinical efficacy. Covering only about 30% of the mass balance, these characterized compounds are accompanied by a larger fraction of additional compounds, which might also contribute to the clinical efficacy and safety of the extract. As part of our systematic research to fully characterize the constituents of Ginkgo extract EGb 761, we focus on the structural class of proanthocyanidins in the present study. Structural insights into the proanthocyanidins present in EGb 761 and a quantitative method for their determination using HPLC are shown. The proanthocyanidins were found to be of oligomeric to polymeric structure, which yield delphinidin and cyanidin as main building blocks after acidic hydrolysis. A validated HPLC method for quantification of the anthocyanidins was developed in which delphinidin and cyanidin were detected after hydrolysis of the proanthocyanidins. The content of proanthocyanidins in Ginkgo extract EGb 761 was found to be approximately 7%.
Keywords: EGb 761; quality; Ginkgo biloba; Ginkgoaceae; proanthocyanidins; HPLC